Дослідження впливу параметрів технологічних схем очисних робіт на стійкість виробок при реалізації концепції «малих шахт» - Сахно, С. В.; Бородіч, В. В.; Карлов, Є. К.; Sakhno, S. V.; Borodich, V. V.; Karlov, Ye. K. (Донецький державний технічний університет, 2020)
Мета. Дослідження впливу параметрів технологічних схем виймання вугілля на напружено-деформований стан порід, що вміщують виробки, при реалізації концепції «малих шахт».

Purpose. Investigation of the influence of the parameters of technological schemes of coal mining on the stress-strain state of the rocks containing the mine roadways in the implementation of the concept of «small mines».
Study of the influence of parameters technological schemes of excavation on the sustainability of mine roadways when implementing the concept of «small mines»
Keywords: напруження; деформації; виробка; вугільна шахта; технологічна схема робіт; stresses; deformations; development; coal mine; technological schemes of excavation